2012
DOI: 10.1111/j.1529-8817.2011.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF IRON LIMITATION ON THE PHOTOPHYSIOLOGY OF PHAEOCYSTIS ANTARCTICA (PRYMNESIOPHYCEAE) AND FRAGILARIOPSIS CYLINDRUS (BACILLARIOPHYCEAE) UNDER DYNAMIC IRRADIANCE1

Abstract: The effects of iron limitation on photoacclimation to dynamic irradiance were studied in Phaeocystis antarctica G. Karst. and Fragilariopsis cylindrus (Grunow) W. Krieg. in terms of growth rate, photosynthetic parameters, pigment composition, and fluorescence characteristics. Under dynamic light conditions mimicking vertical mixing below the euphotic zone, P. antarctica displayed higher growth rates than F. cylindrus both under iron (Fe)-replete and Fe-limiting conditions. Both species showed xanthophyll de-ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
104
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 105 publications
(250 reference statements)
32
104
2
Order By: Relevance
“…The Fe addition bioassay experiments showed that greater Fe availability increased all photosynthesis parameters, including F v /F m , P * max , and a*, similar to results from culture experiments on Phaeocystis antarctica (Strzepek et al, 2012;Alderkamp et al, 2012b;Van Leeuwe and Stefels, 2007). On the other hand, increased light availability in the bioassay experiments increased P * max , but decreased a* and F v /F m .…”
Section: Fe Availability As the Main Driver For Phytoplankton Photosysupporting
confidence: 75%
See 2 more Smart Citations
“…The Fe addition bioassay experiments showed that greater Fe availability increased all photosynthesis parameters, including F v /F m , P * max , and a*, similar to results from culture experiments on Phaeocystis antarctica (Strzepek et al, 2012;Alderkamp et al, 2012b;Van Leeuwe and Stefels, 2007). On the other hand, increased light availability in the bioassay experiments increased P * max , but decreased a* and F v /F m .…”
Section: Fe Availability As the Main Driver For Phytoplankton Photosysupporting
confidence: 75%
“…The initial input ratios (Table 1A) consisted of specific pigment ratios for eight phytoplankton classes that generally dominate Antarctic waters (Wright et al, 2010), including prasinophytes, chlorophytes, cryptophytes, diatoms (with a separate class for Chl c 3 containing diatoms such as Pseudonitzschia), dinoflagellates, and two classes of P. antarctica. The two classes of P. antarctica account for variations in pigment ratios between strains (Zapata et al, 2004) and changes in response to Fe limitation (Van Leeuwe and Stefels, 2007, DiTullio et al, 2007, Alderkamp et al, 2012b. The pigment ratios in the output matrix (Table 1B) were within those reported in the literature (Zapata et al, 2004, Van Leeuwe and Stefels, 2007, DiTullio et al, 2007, Wright et al, 2010, Alderkamp et al, 2012b.…”
Section: Pigment Analysissupporting
confidence: 69%
See 1 more Smart Citation
“…Studies have shown that haptophytes are better adapted to low light and are more prone to photoinhibition compared to diatoms that are better acclimated to high light (Arrigo et al, 2000;Kropuenske et al, 2010). The study by Alderkamp et al (2012) has also shown that haptophytes produced higher ratios of (DDþ DT)/TChl-a than diatoms under ironlimited conditions. Similarly, significantly lower F v =F m , F v =F o , 1=τ Qa , and higher σ PSII observed in the region north of the APF could have been due to the high abundance of nanophytoplankton in this region.…”
Section: Contrasting Photoacclimation Response In Haptophytes-and Diamentioning
confidence: 65%
“…In contrast, under low iron high light conditions, photoinhibition or photodamage may occur as iron limitation decreases the synthesis of cytochrome b 6 f complexes, an enzyme required in the activation of photoprotective mechanisms (Strzepek and Harrison, 2004;van de Poll et al, 2009). Thus, iron-limited cells are less efficient at coping with an environment with rapid irradiance fluctuations than iron-replete cells (Strzepek and Harrison, 2004;van de Poll et al, 2009;Alderkamp et al, 2012). In addition, under iron-Si(OH) 4 colimitation conditions, growth of non-silicious, iron-efficient phytoplankton species such as eukaryotic picoplankton and cyanobacteria often dominate over larger cells (Hutchins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%